The Pandemic Context and Quality of Life for Youth in Constanta County - Sălceanu, Claudia; Călin, Mariana Floricica (Technium Social Sciences Journal, 2022)
The COVID-19 pandemic had an unprecedented impact on Romanian people. For almost two years the changes in the everyday life of the inhabitants of our country happened with such speed and dramatic consequences, that it raised the question about the perception of Romanian people regarding their perceived quality of life. A sample of 1796 young people, all residents of Constanta County, aged between 18 and 25 years old, was assessed with a survey made by the authors, concerning their perception on the quality of their life in the fields of health, self-esteem, goals and values, financial, professional, leisure, learning, family and social environment, and emotional regulation. Of all the themes we studied, this research tries to identify the differences regarding the quality of life between rural and urban residents. We obtained statistical significant differences regarding goals and values, learning opportunities and emotional regulation. Results are discussed in the end of the paper in the context of the on-going changes still caused by the Covid-19 pandemic